Physiologic brain dysmaturity in late preterm infants - Scher, Mark S. (2011)
Neonatal EEG sleep was used to determine if differences are expressed between healthy late preterm and full term groups. Twenty-seven 24-channel multi-hour studies were recorded at similar post–menstrual ages (PMA) and analyzed for eight asymptomatic late preterm infants (LPT) compared with nineteen healthy full term (FT) infants as a preliminary analysis, followed by a comparison of a subset of 8 FT infants, matched for gender, race, and PMA. Z scores were performed on data sets from each group pair comparing each of seven EEG/Sleep measures for entire recordings, active (AS) and quiet sleep (QS) segments and artifact-free intervals. Six of seven measures showed differences between the 8 LPT and 8 matched FT cohort pair comparisons of >0.3; REMs, arousals during QS, spectral correlations between homologous centro-temporal regions during QS, spectral beta/alpha power ratios during AS and QS, a spectral measure of respiratory regularity during QS, and sleep cycle length. Quantitative neurophysiologic analyses define differences in brain maturation between LPT and FT infants at similar PMA. Altered EEG/Sleep behaviors in the LPT are biomarkers of developmental neuroplasticity involving interconnected neuronal networks adapting to conditions of prematurity for this largest segment of the preterm neonatal population.